Neutrophil-Lymphocyte Ratio and Nutritional Status as Parameters of Sputum Conversion in MDR-TB Before & After 3 Months of Anti-TB Treatment - Regina, Putri Maria; Silaen , Johan Christian; Sembiring, Susi (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: The prolonged duration of tuberculosis (TB) treatment has led to an increase in non-compliance among TB patients undergoing anti-TB treatment, consequently leading to treatment failure and drug resistance, notably multidrug-resistant TB (MDR-TB). Individuals with poor nutritional status may elevate the risk of delayed sputum conversion in MDR-TB patients. The neutrophil-lymphocyte ratio (NLR) represents a laboratory parameter with potential as a prognostic indicator in patients suspected of TB infection. Methods: This was an analytical study with a cross-sectional design. The sample was drawn from the medical records of MDR-TB patients at Haji Adam Malik General Hospital, Medan, from October 2022 to March 2023 resulting in a total of 83 samples. Data analysis was performed using Statistical Package for the Social Sciences (SPSS) version 25 software, and bivariate analysis was conducted using paired t-test. Results: Out of 83 MDR-TB patients, 50 (60.2%) were male. Based on nutritional status before three months of anti-TB treatment, the most common nutritional status was normal with 22 individuals (26.5%) and severely underweight with 36 individuals (43.4%). Following three months of anti-TB treatment, the majority had normal, totaling 39 individuals (47%). A total of 67 individuals (80.7%) experienced sputum conversion. The results indicated a significant difference between NLR before and after three months of anti-TB treatment (p = 0.000), as well as a significant difference between nutritional status before and after three months of anti-TB treatment (p = 0.012) at Haji Adam Malik General Hospital, Medan. Conclusion: Significant differences were observed in NLR and nutritional status before and after three months of anti-TB treatment.